Identification and synchronization of chaotic and hyperchaotic systems using Lyapunov Stability Theory - Gularte, Kevin Herman Muraro (2021)
Tese (doutorado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2021.